From Awareness to Empowerment: The Role of Waqf Literacy in Indonesia’s Socioeconomic Ecosystem - Agus Setiawan, Muhammad; Haseena Armina, Sheema; Muhammad Moi, Rizqi; Muna, Izzatul (MD Research Center, 2025)
The Waqf Awareness Movement, launched by the International Center of Awqaf Studies, aims to enhance the understanding and participation of students and the Indonesian public in waqf practices. This study employs a literature review method, analyzing previous studies and academic literature related to the waqf awareness movement and its socio-economic impacts. By synthesizing various scholarly sources, this research explores how education, socialization, and access to information have contributed to increasing public awareness and participation in waqf. The findings indicate that waqf holds significant potential to improve community economic empowerment, strengthen social welfare, and promote solidarity. Furthermore, the literature review reveals that increased engagement in waqf extends beyond donations to include the management and utilization of waqf assets for community development. This study highlights the important role of educational and socialization initiatives in raising awareness of waqf's benefits, aiming to encourage greater public participation. The research emphasizes the need to strengthen these initiatives to maximize waqf's contribution as a tool for sustainable social and economic development. Through deeper understanding of waqf, the public is better prepared to regard it as an effective instrument for community advancement, reinforcing social values, and promoting solidarity.